Obesity, metabolic health and clinical outcomes after incident cardiovascular disease: A nationwide population‐based cohort study - Ralph K. Akyea; George Ntaios; Wolfram Doehner (Wiley, 2023)
Abstract Background The association between metabolic syndrome and increased cardiovascular disease (CVD) risk is well‐established. However, in patients with incident CVD, the relationship between obesity, metabolic health, and subsequent CVD and mortality outcomes are less well‐established. This study investigated the association between body mass index (BMI), metabolic health and the risk of subsequent cardiovascular mortality and morbidity outcomes in patients with incident CVD events. Methods This cohort study identified 130 685 patients from the nationwide Clinical Practice Research Datalink (CPRD GOLD) and Hospital Episode Statistics (HES) databases in the United Kingdom. Patients were ≥18 years with incident CVD [coronary heart disease (CHD), stroke, or peripheral vascular disease (PVD)] between 1 January 1998 and 31 December 2017. BMI (in kg/m2) was categorized as underweight (<18.5), normal (18.5-24.9), overweight (25.0-29.9) and obese (≥30). Within each BMI category, patients were grouped by increasing count of 1, 2 or 3 metabolic risk factors [RF] (dyslipidaemia, diabetes mellitus and hypertension) and were regarded as metabolically unhealthy while absence of these factors was considered metabolically healthy (MH). Multivariable Cox regression was used to assess the risk (hazard ratio with 95% confidence interval) of subsequent outcomes (non‐fatal CHD, stroke, PVD, incident heart failure, CVD‐mortality and all‐cause mortality) in BMI subgroups with incremental count of metabolic RFs. Results During a median follow‐up of 13.0 years, a higher BMI was associated with reduced risk for stroke, PVD, CVD‐mortality and all‐cause mortality within each metabolic risk category, while increasing metabolic RFs within each BMI subgroup accounted for increasing risks. When compared with patients with normal BMI and no RF, CVD‐mortality risk in overweight patients with no RF was 0.76 (0.70-0.84), and in obese patients with no RF was 0.85 (0.76-0.96). The respective risk for all‐cause mortality in patients with overweight and no RF was 0.69 (0.65-0.72), and in obese patients with no RF was 0.75 (0.70-0.79). Subsequent outcomes of stroke and PVD showed similar trends. In contrast, the risk of subsequent non‐fatal CHD events and incident HF increased with higher BMI and with incremental metabolic risk factors within each BMI category. Underweight was constantly associated with increased risk for all outcomes regardless of the presence of metabolic RFs except for non‐fatal CHD events. Conclusions In patients with incident CVD, overweight and obesity were related to a more favourable prognosis for subsequent stroke, PVD and mortality (CVD‐related and all‐cause) irrespective of the presence of other metabolic risk factors.